Children of the Old Testament - Anonymous (Salt Lake City, UT : Project Gutenberg, 2007)
"Children of the Old Testament" by Anonymous is a collection of stories intended for children, written in the early 20th century. The book retells well-known tales from the Old Testament, featuring foundational biblical figures such as Joseph, Moses, Ruth, and Samuel. Aimed at a young audience, it not only provides narratives from scripture but also seeks to impart moral lessons through the actions and faith of these characters. The opening of the book introduces the story of Joseph the Dreamer, depicting his life as the favorite son of Jacob and detailing his relationships with his brothers. It highlights Joseph's struggles, from the jealousy of his siblings due to their father's favoritism and his special coat, to the pivotal moment when his dreams of grandeur spark their ire, leading to his descent into slavery. As the narrative unfolds, it lays the groundwork for the trials Joseph will face and his journey towards becoming a significant figure in Egypt, setting the stage for themes of betrayal, faith, and eventual redemption that will resonate throughout the various stories in the book. (This is an automatically generated summary.)
Release date is 2007-07-28
Produced by Al Haines
Keywords: Bible stories -- Old Testament; Bible. Old Testament -- Biography -- Juvenile literature; Children in the Bible -- Juvenile literature